2014
DOI: 10.1371/journal.pone.0108057
|View full text |Cite
|
Sign up to set email alerts
|

AKT1 and SELP Polymorphisms Predict the Risk of Developing Cachexia in Pancreatic Cancer Patients

Abstract: Pancreatic ductal adenocarcinoma (PDAC) patients have the highest risk of developing cachexia, which is a direct cause of reduced quality of life and shorter survival. Novel biomarkers to identify patients at risk of cachexia are needed and might have a substantial impact on clinical management. Here we investigated the prognostic value and association of SELP-rs6136, IL6-rs1800796 and AKT1-rs1130233 polymorphisms with cachexia in PDAC. Genotyping was performed in DNA from blood samples of a test and validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 45 publications
3
41
0
Order By: Relevance
“…In the present study, SELP and AKT1 SNPs were analyzed and significant association was found on AKT1, where the risk of 5% weight loss in patients with the AKT1 A allele significantly increased. This finding was in the same trend as that reported by Avan et al [4], suggesting that the AKT1 A allele may play a key role in the development of cancer cachexia. There were no significant effects of the SNPs examined on patients' survival, presumably due to the relatively smaller sample size of the present study.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the present study, SELP and AKT1 SNPs were analyzed and significant association was found on AKT1, where the risk of 5% weight loss in patients with the AKT1 A allele significantly increased. This finding was in the same trend as that reported by Avan et al [4], suggesting that the AKT1 A allele may play a key role in the development of cancer cachexia. There were no significant effects of the SNPs examined on patients' survival, presumably due to the relatively smaller sample size of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…One previous study suggested that SELP and AKT1 polymorphisms may play roles in the risk of cachexia and death in pancreatic ductal adenocarcinoma patients (PDAC) in Caucasians [4]. In the present study, SELP and AKT1 SNPs were analyzed and significant association was found on AKT1, where the risk of 5% weight loss in patients with the AKT1 A allele significantly increased.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations